DYNAMIC MORPHOLOGICAL CHANGES IN THE STOMACH IN THE CONTEXT OF ULCERATIVE COLITIS: AN EXPERIMENTAL STUDY - Vohidov Bekzod Rafiq o’g’li, (TADQIQOTLAR, 2025)
Abstract This  study  comprehensively  examined  morphological  and  morphometric changes  in  the  gastric  mucosa  and  wall  under  experimental  ulcerative  colitis  (UC) conditions. The experiment was conducted using an animal model in which colitis was induced  with  TNBS.  Histological  examinations  revealed  severe  dystrophic, inflammatory,  erosive,  and  necrotic  changes  in  the  gastric  mucosa,  vascular  and cellular infiltration in the submucosa, and degenerative processes in the muscular layer. These changes significantly impact the structural and functional state of the gastric wall.  The  results  have  practical  significance  for  clinical  gastroenterology  and morphology.